Socio‐cultural differences in Australian primary school children's weight and weight‐related behaviours. Issue 8 (4th June 2013) - Hardy, Louise L; King, Lesley; Hector, Debra; Baur, Louise A
Abstract : Aim: To examine whether there are socio‐cultural differences in overweight/obesity and weight‐related behaviours of Australian primary school children. Methods: Secondary data analysis of the 2010 NSW Schools Physical Activity and Nutrition Survey ( n = 4898). Height and weight were measured. Parents of Year K, 2, 4 children and Year 6 students completed a questionnaire on demographics and weight‐related behaviours. Cardio‐respiratory fitness was assessed by the 20‐meter shuttle run test and categorised as adequately fit or unfit. Children were categorised according to the main cultural/ethnic backgrounds (Middle‐Eastern, Asian and English‐speaking backgrounds) and socio‐economic status (SES) tertile. Results: Within ethnic groups, SES was associated with weight‐related behaviours, but not consistently, and not with body mass index status. Within ethnic groups, the odds were higher among low SES, compared with high SES to be inactive, unfit and have poorer dietary habits. Weight‐related behaviours among each ethnic group also differed by gender. Compared with low SES children from English‐speaking backgrounds, ethnic boys were two times as likely to be overweight/obese, and the odds were significantly higher among ethnic children to be inactive, unfit and have poor dietary patterns. Conclusion: The results indicate the need for obesity prevention initiatives to specifically target and reach children from low SES and Asian and Middle‐Eastern backgrounds, and the importance of ensuring that such initiatives are culturally appropriate and address relevant issues.